2019
DOI: 10.12963/csd.18554
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Usage of Language Skills for Predicting Recovery from Persistent Group in Korean Speaking Children Who Stutter

Abstract: Objectives: Predicting the prognosis of children who stutter during early childhood is critical. Thus, it is of practical and theoretical interest to identify who will recover from stuttering and who will not, yet this is not an easy task due to overlapping surface similarities between these two groups. We investigated whether language skills at the initial visit can predict 18-month outcomes of stuttering severity. We examined both semantic and syntactic profiles that represent cross-linguistic features of Ko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Similarly, in a smaller sample tracked at Iowa (Hollister et al, 2017), researchers found that higher levels of expressive grammatical development over an 18-month period were associated with recovery in a sample of preschool CWS between 28 and 43 months of age. In another small sample of Korean recovered and persistent CWS (Lee et al, 2019), persistently stuttering children showed lower language skills at first visit than those who recovered; slower development of accurate case marker use still distinguished these children from peers who recovered over an 18-month period.…”
Section: Language Factors That Appear To Influence Recovery From Earl...mentioning
confidence: 95%
“…Similarly, in a smaller sample tracked at Iowa (Hollister et al, 2017), researchers found that higher levels of expressive grammatical development over an 18-month period were associated with recovery in a sample of preschool CWS between 28 and 43 months of age. In another small sample of Korean recovered and persistent CWS (Lee et al, 2019), persistently stuttering children showed lower language skills at first visit than those who recovered; slower development of accurate case marker use still distinguished these children from peers who recovered over an 18-month period.…”
Section: Language Factors That Appear To Influence Recovery From Earl...mentioning
confidence: 95%